2009
DOI: 10.1177/112972980901000107
|View full text |Cite
|
Sign up to set email alerts
|

Pre-Operative Vessel Mapping and Early Post-Operative Surveillance Duplex Scanning of Arteriovenous Fistulae

Abstract: This study shows that preoperative vessel mapping provides useful information regarding the choice of AVF. Access surveillance duplex scanning at 6-8 weeks post-operatively is viable and has a high sensitivity and specificity for final outcome of fistula. Identifying AVF with potential problems early means that further intervention or surgery can be planned earlier, which will have a positive impact on patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
45
0
6

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(54 citation statements)
references
References 18 publications
3
45
0
6
Order By: Relevance
“…There is conflicting evidence in the literature, with some studies showing that pre-operative radial artery diameters <1.5e1.6 mm predict early failure, 8,10,11 while other studies similar to this one, using a 2 mm minimum diameter failed to demonstrate an association. 7,16 Similarly, no association was found between cephalic vein diameter and primary radiocephalic AVF failure, probably the result of including patients with a minimum cephalic vein diameter of 3 mm, unlike others who used a minimum diameter of 1.8 mm. 10,11 The present study confirmed the results of two studies showing that in upper arm fistulas that failed to become functional, pre-operative brachial artery diameters were significantly smaller compared with those that became functional 5,14 ; these studies did not provide minimum diameters useful in clinical practice.…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations
“…There is conflicting evidence in the literature, with some studies showing that pre-operative radial artery diameters <1.5e1.6 mm predict early failure, 8,10,11 while other studies similar to this one, using a 2 mm minimum diameter failed to demonstrate an association. 7,16 Similarly, no association was found between cephalic vein diameter and primary radiocephalic AVF failure, probably the result of including patients with a minimum cephalic vein diameter of 3 mm, unlike others who used a minimum diameter of 1.8 mm. 10,11 The present study confirmed the results of two studies showing that in upper arm fistulas that failed to become functional, pre-operative brachial artery diameters were significantly smaller compared with those that became functional 5,14 ; these studies did not provide minimum diameters useful in clinical practice.…”
Section: Discussionmentioning
confidence: 98%
“…16 Regarding optimum minimum venous diameter, patients with a larger vein have a higher probability of functionality, 6 particularly in the presence of a vein >4 mm in diameter, 4,5 although another study failed to demonstrate such an association. 16 The present study also failed to confirm these associations, and this is considered to be the result of appropriate use of preoperative vessel mapping to exclude small and diseased cephalic veins, unlikely to be successfully used for dialysis. Of note, one study on a mixed population showed that AVFs made with small arteries and veins had a higher rate of early thrombosis than those with more advantageous anatomy; however, no minimum diameters were provided.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These studies have shown that at 6-8 weeks postcreation, a Qa of 400-500 ml/minutes had a sensitivity of 67-89%, a specificity of 65-87%, and an accuracy of 75-87% for radio-cephalic AVF success. A blood flow value of 600 ml/minutes for a brachial-cephalic access had a sensitivity and specificity of 89% and 87%, respectively at this same time period (6). These same studies have shown that an AVD at 4-6 weeks in the range of 0.4-0.5 cm correlated with a successful AVF with a sensitivity in the range of 75% and a specificity in the range of 68-75% (5).…”
mentioning
confidence: 54%